MODEL TOKOH AGAMA DALAM PENGEMBANGAN PENDIDIKAN ISLAM (Studi Kasus di Mrican, Jenangan, Ponorogo) - Moh Masduki; Jainul Mustofa (Journal Multicultural of Islamic Education, 2021)
Religious leaders have a considerable influence in the community, because they are considered a place for the community to complain and resolve community problems related to religious teachings. In connection with this, the role of religious leaders is to invite the community to do good deeds and leave all bad deeds to the community. The focus of this research is the pattern of development of Islamic education and the public's view of these religious figures. The type of research used in this study is qualitative, to find data using observation, interviews, and documentation techniques. Meanwhile, to analyze the data used is the data analysis model introduced by Spradley with the following stages: Domain Analysis, Taxonomy Analysis, Componential Analysis, Cultural Theme Analysis. The results of this study illustrate that: 1) KH Murhadi's character is very capable in science and his very simple nature so that the community gives a positive response and support to him in fighting for education in Mrican Village, 2) KH Murhadi uses the organism model in developing Islamic education in Mrican Village, he combines formal education and religious activities together.